Social Construction of Dangdut Lamongan: Identity and Performance of Dangdut Lamongan - Setiyawan, Dimas Bagus; Juwariyah, Anik; Rahayu, Eko Wahyuni (Gondang: Jurnal Seni dan Budaya, 2025)
Lamongan has two different characteristics based on its territory, namely the North dominated by the culture of the Islamic Mataram Kingdom and Demak Kingdom, and South Parts dominated by Ancient Mataram culture. This cultural diversity has a significant impact on the development of dangdut music in Lamongan. This study was carried out to determine the characteristics of dangdut music in Lamongan based on the cultural backgrounds and the characteristics of the people in each region. The method used in this study is a qualitative approach with phenomenology and social construction methods. The results of this study show how public construction is formed through thought that produces a social construction. The social construction process of dangdut Lamongan music can be seen through three stages, namely internalization, objectification, and externalization. Internalization occurs when a culture are penetrated on dangdut music, adopted and becoming part of the social identity of society. The music not only represents entertainment but also cultural values and social norms lowered from generation to generation. Objektivication is visible in objective elements such as musical instruments, and stage performances which form the typical identity of the dangdut Lamongan. Musical instruments such as drum, suling and electronic musical elements in modern dangdut collaborate with traditional musical instruments. Finally, Externalization occurs when people create in accordance with the form of serving their respective regions. Through the three processes, dangdut music in Lamongan becomes a social space where people interact, communicate, and reinforce their cultural identity through music.